Molecular characterization and antibiotic susceptibility of methicillin resistant staphylococcus aureus isolated from chickens and cattle - Magashi, Abbulkadir Magaji (2012)
Staphylococcus aureus has been widely recognized as one of the major human pathogen responsible for a wide range of diseases, ranging from minor skin infections to more life-threatening infections of the central nervous system and respiratory, urinary tract infections and infections associated with internal implanted devices. In animals, S. aureus is implicated as a cause of a number of diseases ranging from pneumonia, osteomyelitis, joint infection and septicemia in poultry, mastitis in cattle and small ruminants. The disclosure of MRSA in pets and domestic animals (pigs, horse, poultry and cattle) with the frequent isolation of livestock associated MRSA among animals and human handlers confirmed the fears that animals may serve as reservoirs for MRSA transmission. Staphylococcus aureus has been established as one of the foremost. Superantigen producing causative agent, when ingested enterotoxin produced is responsible for food poisoning. Consequently food animals colonized with MRSA pose a substantial public health concern. The initial part of this study was designed to isolate and characterize S. aureus with the aid of conventional and molecular methods. A total of 450 feather samples were collected from chickens in nine designated broiler farms from three states in Peninsular Malaysia, between April 2007 to November, 2008 and 150 nasal swabs from cattle were also collected from three farms. Conventional phenotypic tests used included gram staining, biochemical tests and DryspotStaphytect plusagglutination kit (DR0M100 UK) to identify S. aureus. The identified isolates were inoculated on selective media (mannitol salt agar and oxacillin resistance screening agar) for the detection of MRSA from chickens and cattle samples. Based on the biochemical tests and characteristic growth on the selective media, 153 (34%) and 17 (11.33%) isolates were identified as MRSA from chickens and cattle respectively. Polymerase chain reaction assay for the detection of mecA and nucA genes confirmed 66 as MRSA out of the 170 MRSA identified using conventional test. The overall prevalence of MRSA and MRS from chickens was reported as 13.56% (95%CI 0.0179-0.0503). Low prevalence of MRSA/MRS from cattle farms was observed with the overall prevalence of MRSA from cattle reported as 3.33% (95%CI 0.0080-0.0603) and 5.33% (0.0157-0.0786) for MRS respectively. Statistical analyses were carried out to compare differences between slide coagulase and DryspotStaphytect kit using chisquare test. There was no significant difference between the two tests at p = 0.05, x2 = 0.1662. Norminal logistic regression was used to compare differences between the tests, animal’s species and farms. The likelihood ratio chi-square showed that slide coagulase p = 0.349, DryspotStaphytect kit p = 0.938 and PCR p = 0.082 had no significant relationship with animal species; whereas farms had a significant relationship with the tests p ˂0.0001. The second part of the study investigated the in vitro antimicrobial susceptibility of the MRSA, MRS and MSSA to 30 antimicrobial agents and the determination of oxacillin MIC using E-test strips (AB Biodisk Sweden). The oxacillin MIC for chicken MRSA ranged from 0.5μg/L to ≥256μg/L. Using the break point for oxacillin resistance by CLSI (2006) ≥4μg/L, 42 MRSA (68.85%) were considered fully resistant and 19 (31.15%) had MIC below the set standard. Comparably 41 MRS were considered resistant based on the CLSI criteria for oxacillin E-test and 20 isolates had lower MIC. The MIC for cattle MRSA isolates ranged from 1-256μg/L based on CLSI cut off 2 isolates were susceptible. The pattern of resistance that is common among the MRSA cut acrossoxacillin, cefoxitin, tetracycline, clindamycin, lincomycin, neomycin, erythromycin, penicillin G, streptomycin and cefuroxime. All the 170 isolates were susceptible to linezolid; furthermore most of the isolates were susceptible to mupirocin and teicoplanin with the exception of two MRSA and two MRS. The genetic background of some selected isolates using different types of typing methods such as multilocus sequence typing (MLST), spa typing, pulse field gel electrophoresis (PFGE) and pyrogenic toxin genes screening was investigated.MLST characterized 12 MRSA isolates into 11 sequence types, namely ST9, ST15, ST14, ST537, ST190, ST194, ST795, and ST1279 from chickens while ST59, ST35 and ST573 from cattle. These 12 isolates were grouped into five spa types’ t437, t442, t360, t189 and t5696. The analysis of PFGE macrorestriction patterns percentage of similarity identified from the dendogram at 80% similarity coefficient was used to define pulsotypes. The PFGE analysis identified 22pulsotypes with nine sub types and the most common cluster is C which appeared to be present in four farms. Cluster B was similar albeit having different spa types. Diversity ensued among the isolates from chickens due to occurrence of more than two pulsotypes,’ no genetic diversity was observed among the cattle isolates. Thirty staphylococcal isolates (including 27 MRSA and 3 MRS) were screened for the presence of 10 pyrogenic toxin genes. Nine of the 27 (90%) (27/30) MRSA harbored 1 to 5 toxin genes. One organism (ST537, t437) possessed five genes sed + seg + sei + sea + sej, the most predominant toxin genes are seg + sei (20%) (egc cluster). Toxic shock syndrome toxin genes (tsst-1) were found in two (2/30) (6.67%) MRSA and one MRS isolate (1/30) (3.33%). No toxin genes were found in all cattle isolates. This investigation confirmed the presence of MRSA and MRS from chicken and cattle in Malaysia which was not reported previously. Antibiotic sensitivity tests found more prevalent resistance among the isolates to oxacillin, cefoxitin, erythromycin, cefuroxime, lincomycin, clindamycin, streptomycin, tetracycline and penicillin. Screening of the staphylococcal enterotoxin genes discovered the presence of classical toxin genes (sea, sed and tsst) and preponderance of newly described toxin genes, which are both implicated in staphylococcal food poisoning. This study highlighted that food animals could serve as a vehicle for the transfer and disseminations of antibiotic resistant bacteria with enterotoxigenic potential to the public thereby making clinical treatment difficult and expensive.